Um espaço "Entre" o urbano e o rural : $b representações visuais de São Leopoldo, Taquara e Novo Hamburgo (RS) 1889-1930 - Müller, Alex Juarez (2015)
This research analyzes the urbanization process of the following cities, São Leopoldo, Taquara and Novo Hamburgo (RS) located in Vale dos Sinos during the First Republic (1889-1930). The time delimitation, although it presents a political cut, was chosen because it represents the period in which urban projects guided by European modernity are spread throughout the country. The new political status conquered by the immigrants colonization of the region favor the realization of such projects at local level. Is also at this time that the photographs of urban landscapes intensify production at local level, and national. The study has the objective of understand, through the urban landscape shots, the representations constructed by the image in the context of delimitation of local urban life to the time modernity standards. The use of photography as source and object of research makes possible new approaches to urban development, constituting an historical and visual narrative of public photographs of the urban, which intersection with other narrative forms broaden the understanding of the historical process under study. The concepts of city and modernity are essential for the development of this research, as well as the methodological and theoretical aspects that involve the use of photography as a historical source. The choice of photographs was guided first by the identification of urban landscape images in "local collections" and "specific of German immigration"; after the selection of the places that were more registered by photographers; and, finally, it was observed between the repeated collections photographs showing reproduction and circulation. The study is a comparative analysis concerning urban landscape photographs of the three cities to identify similarities and differences between them. It also aims to identify the relationship between the modernization process of Brazilian cities and the world as the one found in the studied cities. Therefore, urban photographs reveal aspects related to modernity, as a global phenomenon and, at the same time, to local particularities.